CHARITY FOR THE AUTONOMOUS SELF - Esbeck, Carl H. (Journal of law and religion, 2017)
Australia adopted the Charities Act of 2013, consolidating and restating the country's governing statutes on the registration and qualification of charities, but leaving to the future any reconciliation between faith-related charities claiming religious liberty and others demanding marriage equality and no discrimination based on sexuality. Concurrent to this development, but with an eye to the direction of charity law in common law systems throughout the world, major works have come to us from two Australian scholars. In this review I offer much about these two monographs, but the discussion that immediately follows concerns the law of charitable nonprofits in the United States, the basic structure of that law, and current issues implicating religious freedom.